A comparison between the concepts of Heuristic Enquiry and Tazkiyat-un-nafs - Cardo, Georgina; Tudor, Keith (European Journal for Qualitative Research in Psychotherapy, 2024)
This article offers a comparison between concepts of heuristic enquiry and tazkiyat-un-nafs, the Islamic concept of self/soul purification and/or reformation of the spiritual heart (qalb). The article outlines key concepts of heuristic research methodology as identified by Moustakas (1990) and Sela-Smith (2002) and elaborated by McCann and Tudor (2024). We reflect on the first author’s experience while undertaking some original research under the supervision of the second author, both of whom share an interest in cultural and religious identity and how this is or is not considered in psychotherapy (Florence et al., 2019; Tudor, 2019). From that original research, in this article, we discuss the concepts of heuristic research as they exemplify heuristic methodology compared with the Islamic practice of tazkiyat-un-nafs, identifying the noticeable differences between them. The article aims to support researchers who consider integrating Islam into their psychotherapeutic research – and, in parallel, their psychotherapy practice; as such, we view this as a contribution to the Islamic psychology and psychotherapy movement.